Real-Time Algorithms and Architectures for several user Channel Detection in Wireless Base Station Receivers - Nitish Meena; Nilesh Parihar (Institute of Advanced Engineering and Science, 2015)
In this paper presents algorithms and architecture designs that can meet real-time requirements of for several user channel estimation and detection in code-division multiple-access-based wireless base-station receivers. Entangled algorithms proposed to implement several user channel assessment and demodulation make their real-time execution difficult on current digital signal processor-based receivers. A based several user channel assessment scheme requiring matrix conversion is draft again from an demodulation perspective for a reduced intricacy, repetitive scheme with a simple fixed-point very large scale integration architecture. A reduced-intricacy, bit-streaming several user demodulation algorithm that avoids the need for demodulation is also developed for a simple, pipelined VLSI architecture. Thus, we develop real-time solutions for several user channel assessment and demodulation for third-generation wireless systems by: 1) designing the algorithms from a fixed-point execution perspective, without significant loss in error rate performance; 2) task partitioning; and 3) designing bit-streaming fixed-point VLSI architectures that explore pipelining, correspondence, and bit-level computations to achieve real-time with minimum area overhead.